PENGARUH KOMPETENSI, INDEPENDENSI DAN UKURAN AUDITEE TERHADAP KUALITAS AUDIT - H., Dwi Agustina; Sudarna, Made; Ludigdo, Unti (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2014)
This study examines and analyzes the influence of competence, independence and the size of the auditees on audit quality. Audit quality is defined as the probability that the auditor will both discover and report a breach in the client’s accounting system. Drivers of audit quality-a framework are : culture within the firm, the skills and personal qualities of audit partners and staff, the effectiveness of the audit process, the reliability and usefulness of audit reporting, factors outside the control of auditors. Competence of auditors is adequate professional proficiency to perform inspection tasks and professional proficiency in the preparation of examination report. In this study, the competence dimension of competence using Certified General Accountant (CGA) are leadership, professionalism and professional knowledge. The independence is the mental attitude and appearance that is free from private interference, and external organizations. The independence consisting of: a long relationship with the auditees and the provision of non audit services and the pressure of the auditees, peer review of auditors. Auditee size is total assets and revenue of each county/city in Java. Using the random sampling method, the research tries to collect some inportant information given by respondents. Questionaire is a tool used to measure the variables. The hypotheses were tested with SPSS. The sample of this study is the Chairman of the audit team LKPD 2010 on the BPK RI in Java. Data obtained by spreading 118 and a total of 110 questionnaires are returned and processed feasible. The results partially demonstrate competence and independence affect audit quality, while the size of the auditee does not affect audit quality. Researchers can then add other indicators in the variable size of auditees such as number of population and area, total spending, the number of programs and activities within one year.